Handbook of the economics of international migration. - Chiswick, Barry R.; Miller, Paul W. (North-Holland, 2015)
The economic literature on international migration interests policymakers as well as academics throughout the social sciences. These volumes, the first of a new subseries in the Handbooks in Economics, describe and analyze scholarship created since the inception of serious attention began in the late 1970s. This literature appears in the general economics journals, in various field journals in economics (especially, but not exclusively, those covering labor market and human resource issues), in interdisciplinary immigration journals, and in papers by economists published in journals associated with history, sociology, political science, demography, and linguistics, among others.